MEMBATIK BERSAMA DIFABELZONE.ID: PERUBAHAN PERSPEKTIF TERHADAP DIRI PENYANDANG DISABILITAS MELALUI INTERAKSI SOSIAL YANG INKLUSIF - Siti Putri Lestari (UNIVERSITAS SEBELAS MARET (UNS), 2024)
The batik workshop with people with disabilities in the Difabelzone.Id community is an interesting phenomenon to study. People with disabilities become batik mentors, while visitors become their students. In this activity, there is direct interaction between visitors and people with disabilities, which shows a blurring of space between normal and inclusion spaces. This paper describes how the interaction in the batik workshop at Diffablezone.Id changes the perspective of people with disabilities towards themselves. How is the interaction able to bring visitors into the inclusion space? This research uses qualitative and ethnographic methods, using George Herbert Mead's symbolic interaction theory framework. Data collection techniques were carried out through participant observation, semi-structured in-depth interviews, documentation, and literature study. The results showed that the interaction in the batik workshop activities was able to change and create new meanings for people with disabilities. Initially, they were insecure and exclusive in becoming secure and open to many people; this was due to the exchange of symbols between the two, who could fight the stigma and negative stereotypes attached to them. The interaction also creates a mentor-student relationship between visitors and people with disabilities that can bring visitors into the inclusion space. They interact directly and experience an environment different from their own, creating a deeper understanding of them. In addition, the batik workshop activity creates an inclusive space through direct social interaction.